Growth and Development Education on Parents' Understanding Level of Gross Motor Development in Children Aged 0-6 Months - Naufal, Adnan Faris; Nabila, Aulia Safa; Susilo, Taufik Eko; Fatmarizka, Tiara; Awanis, Almas; Yuliani, Diki Retno (Academic Physiotherapy Conference Proceeding, 2023)
The growth and development of children aged 0-6 months is an important stage to achieve optimal quality of life. Parents have an important role in stimulating child growth and development early on in child growth and development. Problems that occur in children of this age, one of which is gross motor development due to parents' lack of understanding of child development. Education in the form of health literacy discusses growth and development and how to stimulate according to age so that parents can apply what has been taught. The aim is to determine changes in the level of understanding of parents when given growth and development education about gross motor development of children aged 0-6 months. This study used a quantitative research design with a type of quay experimental research, a one- group pre-test-post-test approach. The number of samples was 44 respondents with the purposive sampling method. The variables of this study are independent, namely parents' understanding of child growth and development measured by questionnaires, and dependent variables, namely gross motor development of children aged 0-6 months measured by ASQ (Ages and stages questionnaire). Data analysis techniques used were univariate test, normality test, and effect test. The effect test using Wilcoxon showed the sig result (2-tailed) was 0.000 <0.05, meaning there is a significant effect. It can be concluded that there is an effect of growth and development education on parents' level of understanding about the gross motor development of children aged 0-6 months.